A Case of Atypical Neurofibromatous Neoplasm of Uncertain Biologic Potential: Unravelling the Enigma - Apoorva Pande; Samarth Shukla; Sourya Acharya; Pravin Gadkari; Milind Pande (Journal of Clinical and Diagnostic Research)
Neurofibromatoses are a group of genetic disorders that cause tumours to form on the nerve tissue. These tumours can progress to more proliferative lesions and can also eventually become malignant, giving rise to a Malignant Peripheral Nerve Sheath Tumour (MPNST). The authors describe a rare case involving a 27-year-old female who presented with swelling on the left forearm in the surgery Outpatient Department (OPD). The swelling measured 6×5 cm and was noted on the left upper forearm. The overlying skin appeared normal, with no evident pulsations. Notably, a scar mark indicative of a previous surgery for a similar swelling was observed at the same site. The patient reported that the previous swelling was operated 2 years ago. Magnetic Resonance Imaging (MRI) findings indicated fusiform swelling in the mid-forearm, possibly originating from the ulnar nerve with significant involvement of the adjacent structures. This case underscores the complexity and diagnostic challenges associated with such swellings, necessitating thorough examination and ongoing monitoring for timely intervention. This case highlights the importance of thorough clinical evaluation, histopathological examination, and molecular analysis in accurately characterising such tumours, guiding clinical management decisions, and ensuring optimal patient outcomes. The diagnostic evaluation and analysis of such swellings contribute invaluable information regarding their proliferation rate and propensity for malignant progression. This comprehensive understanding aids clinicians in tailoring management approaches that prioritise minimal invasiveness while effectively addressing the potential for malignancy, thus optimising patient care.